Selfie in the opinions of respondents in the Polish-Czech borderlands - Krzysztof Zajdel (Jan Dlugosz University, 2022)
This article deals with the selfie phenomenon among a significant percentage of young people. The main objective of my research took the form of questions: - how much of the study group takes selfies and posts them on social media? - how much does possible satisfaction/lack of satisfaction with life result in taking a selfie? Research strategy: two groups of students: from Poland and the Czech Republic. Purposive random selection. The research method is a diagnostic survey, the technique is a questionnaire, while the tool is a survey questionnaire consisting of extensive 15 questions. I found it interesting to compare the two groups of respondents, that is, young people from Poland and the Czech Republic. I tried to find out why they do so and whether it is due to, for example, satisfaction with life. I tried to look for differences on both sides of the border, if any.